2015
DOI: 10.4103/0976-5042.165723
|View full text |Cite
|
Sign up to set email alerts
|

Primary gastric tuberculosis mimicking a submucosal tumor

Abstract: Gastric tuberculosis is very rare and is usually associated with pulmonary tuberculosis. Endoscopically, it usually resembles peptic ulcer disease or malignancy. We present a 28-year-old female who had a submucosal lesion in the body of the stomach that mimicked a submucosal tumor. Endoscopic ultrasound guided fine needle aspiration yielded caseous material, and the cytological examination confirmed the diagnosis of tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Endoscopic biopsy has a poor yield even in ulcerated lesions and endoscopic biopsy rarely reveals granulomas because of the predominantly submucosal location of these lesions and the failure of routine endoscopic biopsies to include the submucosa [ 17 ]. The diagnosis of duodenal TB is usually made after surgical intervention (exploratory laparotomy) and it is very rarely made preoperatively [ 25 ]; however, Sharma et al reported that endoscopic ultrasonography (EUS) is an excellent modality for characterizing the lesion, as well as obtaining a sample for cytological confirmation of the diagnosis [ 26 ]. Multiple intraoperative fine-needle aspiration cytology (FNAC) may be taken from the diseased portion of the duodenum to establish the histopathological diagnosis if not established by any other means [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic biopsy has a poor yield even in ulcerated lesions and endoscopic biopsy rarely reveals granulomas because of the predominantly submucosal location of these lesions and the failure of routine endoscopic biopsies to include the submucosa [ 17 ]. The diagnosis of duodenal TB is usually made after surgical intervention (exploratory laparotomy) and it is very rarely made preoperatively [ 25 ]; however, Sharma et al reported that endoscopic ultrasonography (EUS) is an excellent modality for characterizing the lesion, as well as obtaining a sample for cytological confirmation of the diagnosis [ 26 ]. Multiple intraoperative fine-needle aspiration cytology (FNAC) may be taken from the diseased portion of the duodenum to establish the histopathological diagnosis if not established by any other means [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…For suspected gastric tuberculosis, multiple deep biopsies, repeated biopsies, EUS-guided fine-needle aspiration or EUS-guided fine-needle biopsy (EUS-FNA or EUS-FNB) [13] should be performed. The first two patients underwent repeated deep excavation biopsy along the central erosion of the lesions and received a final diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a report of 10 patients of whom 9 underwent dilatation, there was like lymph nodes which may cause luminal narrowing or bulge with normal overlying mucosa. 1,7 The availability of endoscopic ultrasound provides a modality to access and sample such lesions. 7 To conclude, endoscopic diagnosis is feasible in duodenal tuberculosis and patients respond well to the standard ATT while some patients may need dilatation of GOO.…”
Section: Discussionmentioning
confidence: 99%